Complete mitochondrial genome of Saiga tatarica (Ruminantia; Pecora; Bovidae) isolate Wuwei in China. Issue 2 (12th December 2017) - Ding, Xin; Wu, Jin; Xiao, Hui; Wang, Zhaojun; Liu, Qi; Liu, Xuedong; Jin, Kun; Zheng, Dong
Abstract: This report described the complete mitochondrial genome of the Saiga antelope, Saiga tatarica, from the Gansu Endangered Animal Research Center (GEARC) in Gansu Province, China. The mitogenome was a circular molecule of 16, 376 bps (Genbank accession number: MF497028). It contained 13 protein-coding, 22 tRNA and two rDNA genes. The protein-coding genes had ATA or ATG as the initiation codon, and were terminated by the typical stop codon TAA, except for NAD2 and NAD3. The complete mitogenome sequence would be useful for further understanding origination, evolution and conservation genetics of S. tatarica population in China.